Effectiveness of Mini-CEX as an assessment tool in Pediatric Postgraduate Residents’ Learning.: - Ehsan, Shaista; Usmani , Ambreen (Journal of Liaquat University of Medical & Health Sciences, 2023)
Objective: To determine the effectiveness of Mini-CEX as a formative assessment instrument in improving the clinical skills of postgraduate residents in Pediatrics. Methodology: This cross-sectional study was conducted from January to August 2021 at Ziauddin Medical University. A total of 176 Mini-CEX encounters were conducted on twenty-two Pediatric postgraduate residents by eight faculty members. The non-probability convenience technique was used for sampling. Each resident underwent one Mini-CEX encounter per month, and the ratings were recorded. An Objectively Structured Clinical Evaluation (OSCE) was conducted before the first Mini-CEX session, and the last and the mean scores were compared. Data were analyzed using SPSS version 20. ANOVA was used to determine inferential statistics to calculate the p-value and the improvement in score over time to report statistical significance. Results: Mean scores of all clinical competencies improved with subsequent Mini-CEX sessions. Maximum improvement was noted in clinical management skills and organization/efficiency. Marked improvement was observed in OSCE scores before the first Mini-CEX session and after the eighth session (p-value <0.001). An increase in the satisfaction rate of both faculty and residents with each subsequent Mini-CEX session was also noted. Conclusion: Mini-CEX effectively improves pediatric postgraduate residents’ clinical learning; therefore, it should be incorporated into the national residency program.